Wide Load Range ZVS Three-level DC-DC Converter: Modular Structure, Redundancy Ability, and Reduced Filters Size - Yong Shi (Energies, 2019)
In future dc distributed power systems, high performance high voltage dc-dc converters with redundancy ability are welcome. However, most existing high voltage dc-dc converters do not have redundancy ability. To solve this problem, a wide load range zero-voltage switching (ZVS) three-level (TL) dc-dc converter is proposed, which has some definitely good features. The primary switches have reduced voltage stress, which is only Vin/2. Moreover, no extra clamping component is needed, which results simple primary structure. Redundancy ability can be obtained by both primary and secondary sides, which means high system reliability. With proper designing of magnetizing inductance, all primary switches can obtain ZVS down to 0 output current, and in addition, the added conduction loss can be neglected. TL voltage waveform before the output inductor is obtained, which leads small volume of the output filter. Four secondary MOSFETs can be switched in zero-current switching (ZCS) condition over wide load range. Finally, both the primary and secondary power stages are modular architecture, which permits realizing any given system specifications by low voltage, standardized power modules. The operation principle, soft switching characteristics are presented in this paper, and the experimental results from a 1 kW prototype are also provided to validate the proposed converter.